Instrumentos Financieros - Un Camino Hacia El Mercado De Derivados En El Comercio Internacional En Colombia (2025)
When discussing risks, volatility in exchange rates, prices, and even in the market, it is also about finding a solution or rather a mechanism that mitigates or addresses all these anomalies. This is why investors, savers, economic agents, large companies, and others turn to the financial derivatives market, utilizing instruments such as futures, options, forwards, and swaps, not only for the aforementioned reasons but also to achieve profit or returns, manage risks, and speculate on price movements.